Undetected circulation of major arboviruses in West Sudan: urging for institutionalizing multisectoral one health strategy for the preparedness, prevention, and control of zoonotic arboviral diseases - Nouh Saad Mohamed; Emmanuel Edwar Siddig; Claude Mambo Muvunyi; Abdualmoniem Omer Musa; Adel Elduma; Ayman Ahmed (BMC Research Notes)
Abstract Objectives Arboviruses pose a significant global health challenge. This study investigated the seroprevalence of major human arboviral infections, including yellow fever (YFV), dengue (DENV), Crimean-Congo hemorrhagic fever (CCHF), Rift Valley fever (RVF), West Nile virus (WNV), and chikungunya (CHIK), in Darfur region from September to December 2018. ELISA-IgM was used to detect antibodies. RT‒PCR was used to differentiate YFV infection from vaccine-immuno-response in IgM samples. Results A total of 152 blood samples were collected, with 123 (80.9%) from males and 29 (19.1%) from females. The participants were grouped by age: 50 (32.9%) were under 20 years, 96 (63.2%) were aged 20–45 years, and 6 (3.9%) were over 45 years. The seroprevalence rates for YFV, DENV, and CHIKV were 68 (44.7%), 23 (15.1%), and 5 (3.3%), respectively. There were 11 molecularly-confirmed YFV cases (7.2%). Among these, 3/11 were positive for DENV-IgM, and 1/11 was positive for CHIKV-IgM. Among the 68 YFV-positive individuals, 15 (22.1%) had been exposed to DENV, and 2 (2.9%) had been exposed to CHIKV. Co-exposure to DENV and CHIKV was detected in 3 (1.9%) patients, while 2 (1.3%) patients had triple exposure to YFV, CHIKV, or DENV. No exposure to CCHF, RVFV, or WNV was detected.